Pendampingan Peningkatan Pencegahan Covid-19 Pada Komunitas RW 02 dan Pedagang Pasar Tradisional Modern di Kampung Tangguh Tejo Agung Kota Metro - Riyanto Riyanto; Herlina Herlina; Yoga Tri Wijayanti (Communio: Jurnal Pengabdian Kepada Masyarakat, 2022)
The Covid-19 pandemic globally since the WHO China Country Office in December 2019 is still experiencing an increasing trend and spreading to remote villages or sub-districts. Metro City is one of the pandemic areas because it has become a red zone for the spread of Covid-19, including the Tejoagung sub-district in May 2020. The Government has carried out the handling and prevention of the Covid-19 pandemic together with Non-Governmental Organizations and the community. In fact, the government has started to use an approach by forming a Tangguh village. However, the Covid-19 pandemic has not shown a decrease in cases. The purpose of this activity is to assist in increasing the prevention of Covid-19 in the RW 02 community and traditional market traders in Tejo Agung Metro Timur tough village, Metro city. The method of implementing the activity is carried out by the stages of preparation, implementation and evaluation. The target of the activity is the RW 02 community and traditional market traders in the Tejo Agung sub-district. This activity resulted in the distribution of 80 masks to traders in the Tejo Agung sub-district traditional market, leaflets, masks and social assistance were distributed to several families which had an economic impact due to the Covid-19 pandemic, strengthening the implementation by the Team of Independent Tough Village Volunteers the New Normal countermeasures Covid-19 Tejo Agung sub-district for implementation of independent isolation. This activity needs continuous follow-up until the period of adaptation to new behaviors and the Covid-19 pandemic can be overcome by the Government together with the community.